(untitled) - Kabala, Thomas (Albany, New York, 2000)
This book introduces to basic electron theory and electron movement, as well as direct current series circuits, parallel circuits, and series-parallel circuits. It presents detailed circuits diagrams and photographs of commonly used electrical devices and materials. It also explains types of electrical conductors and wire sizes; and rotating machinery fundamentals with material on electromagnetism, the generation of electromotive force, and motor principles.
Keywords: Electric circuits,Electric engineering,Electric machinery; Direct current,Direct current